The History of First Century American Legal Education: A Revisionist Perspective - Charles R. McManis (Washington University Law Quarterly, 1981)
In order to create and maintain a rigorous system for training lawyers, legal educators during the past century have felt obliged to take a narrow view of legal education.
Keywords: Law schools; Legal education; Professional education; United States